2021
DOI: 10.7759/cureus.19395
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 and p16 in Carcinoma Breast Tissue: Depicts Prognostic Significance or Coincidence

Abstract: Breast cancer remains the most common malignancy among the Indian female population. The p16 and p53 genes are frequently mutated in breast cancer. Therefore, we aimed to evaluate the prognostic significance of p16 and p53 overexpression in breast cancer and their correlation with various traditional prognostic parameters. Total of 100 confirmed cases of breast cancers were selected. Patients who underwent chemotherapy treatment were excluded from the study. Estrogen receptor (ER), progesterone receptor (PR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Additionally, p53 expression percent showed a significant positive linear correlation with frequent apoptosis, and mild p53 intensity showed a significant relation with advanced nodal stage (N2+N3). Previous studies have declared the association of p53 with poor prognostic parameters including high tumor grade, high Ki-67 proliferation index, Her2neu, and triple-negative expression (41, [45][46][47]. However, it was reported that the p53 mutation did not impact the outcome of breast cancer (48).…”
Section: Association Of the Progression-free Survival And The Clinico...mentioning
confidence: 99%
“…Additionally, p53 expression percent showed a significant positive linear correlation with frequent apoptosis, and mild p53 intensity showed a significant relation with advanced nodal stage (N2+N3). Previous studies have declared the association of p53 with poor prognostic parameters including high tumor grade, high Ki-67 proliferation index, Her2neu, and triple-negative expression (41, [45][46][47]. However, it was reported that the p53 mutation did not impact the outcome of breast cancer (48).…”
Section: Association Of the Progression-free Survival And The Clinico...mentioning
confidence: 99%
“…13 It is a gene that acts as a tumor suppressor biomarker, thus playing a vital part in controlling cell proliferation, genetic stability, and regulating cell growth. 14 When a gene mutation occurs in >50% of all cancers owing to its transformed spatial conformation, 15 such as liver cancer, 16 breast cancer, 17 esophageal cancer, 18 and lung cancer, the ability of TP53 to regulate cells is lost. Consequently, the detection of these protein cancerous biomarkers in various matrices could be used to monitor different human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Screening detects some cancers before they have metastasized, hence by using screening methods such as ultrasound and mammography, conducting self-examination, the age of breast cancer incidence has reduced in the last few years [2] . However, reappearance may be seen in 20%-30% of breast cancer patients despite the employment of the effective therapies based on presented prognostic factors [3] . Tumor markers are molecules occurring in tissues that are associated with cancer.…”
Section: Introductionmentioning
confidence: 99%